Growth Factors BDNF And TGF1Î² in Tissue of Cryopreserved Human Placental Amniotic Membrane after Antiglaucomatous Surgery - Kazmiruk, Irina L.; Demin, Yuriy A.; Ryazantsev, Vladimir V. (Problems of Cryobiology and Cryomedicine, 2016)
The effect of cryopreserved human placental amniotic membrane (HPAM) on the release of cell growth factors BDNF and TGF1Î² into both an environment and eye within the observation period of up to 21 days has been studied. By enzyme immunoassay there was investigated the content of cell growth factors in ocular tissues after use as a coating of the frozen according two-step regimen HPAM in antiglaucomatous surgery. The efficiency of using the frozen-thawed HPAM in respect of releasing the cell growth factors after its application into the post-surgery defect zone has been demonstrated. There was found the dependence of accumulation of growth factors TGF1Î² and BDNF on time of cryopreserved HPAM application, eye tissue type and tropism of growth factors. Â  Probl Cryobiol Cryomed 2016; 26(2):145-154.